2001
DOI: 10.3354/meps224187
|View full text |Cite
|
Sign up to set email alerts
|

High ammonium production from sediments in hypereutrophic shrimp ponds

Abstract: Intensive shrimp ponds are hypereutrophic ecosystems with high nutrient loading rates. The contribution of sediment nutrient fluxes to nutrient cycling in shrimp ponds was studied. Benthic processes were quantified using benthic chambers (clear and dark) on the sediment of intensive shrimp ponds at 3 farms. The ponds contained 2 distinct sediment zones: an outer zone of sand and rubble swept clean by the action of paddlewheels and other aerators (65 to 85% of the pond area), and an inner zone where settled par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
38
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 40 publications
8
38
1
1
Order By: Relevance
“…Denitrification provides a sink in the nitrogen budget and thereby plays an important role in controlling the degree of eutrophication in waters subjected to substantial anthropogenic input of nutrients (Seitzinger 1988;Rysgaard et al 1995). The low DE in BC is consistent with studies in other estuarine systems which have demonstrated that as nutrient loads increase, denitrification removes a smaller proportion of the load (Sloth et al 1995;Burford and Longmore 2001;Caffrey et al 2007). The effect of nutrient loading on DE has important implications for the nutrient status of the system and has flow-on effects that alter the structure of higher trophic levels such as fish and invertebrate communities (Kemp et al 2005).…”
Section: Effect Of Nutrient Loads On Biogeochemical Processessupporting
confidence: 73%
“…Denitrification provides a sink in the nitrogen budget and thereby plays an important role in controlling the degree of eutrophication in waters subjected to substantial anthropogenic input of nutrients (Seitzinger 1988;Rysgaard et al 1995). The low DE in BC is consistent with studies in other estuarine systems which have demonstrated that as nutrient loads increase, denitrification removes a smaller proportion of the load (Sloth et al 1995;Burford and Longmore 2001;Caffrey et al 2007). The effect of nutrient loading on DE has important implications for the nutrient status of the system and has flow-on effects that alter the structure of higher trophic levels such as fish and invertebrate communities (Kemp et al 2005).…”
Section: Effect Of Nutrient Loads On Biogeochemical Processessupporting
confidence: 73%
“…The percentage of loss due to denitrification and ammonia volatilization varies among reports, with estimations as high as 66% (Couch, 1998;Paez-Osuna et al, 1999), and as low as < 2% (Burford and Longmore, 2001). In the present study, the level of volatized ammonia was unclear.…”
Section: Nutrient Budgetcontrasting
confidence: 49%
“…Avnimelech (1995) estimated that the area covered by sediments in typical shrimp ponds in Thailand comprises nearly 50% of the pond bottom and suggested that shrimp growth, activity and health may be negatively affected in this region. Burford and Longmore (2001) found that the sludge zone represented 15-35% located at the center of a 10-ha shrimp. The pore water NH 4 concentration in this zone was 4220-8950 AM, as compared to 560 -1010 in peripherial zone.…”
Section: Effects Of Accumulated Sediment On Shrimp Productionmentioning
confidence: 99%
“…Alongi et al (1999) estimated that the contribution to carbon oxidation was 41-60% through O 2 respiration, 7 -22% from Mn reduction, 5 -25% from iron reduction and 13-26% from sulfate reduction in shrimp pond sediments. Burford and Longmore (2001) reported that 50 -80% of the carbon degradation in shrimp pond soils was anaerobic, mostly coupled with sulfate reduction. Reduced inorganic species may affect biological activity.…”
Section: Redox Reactions In the Pond Bottom Soilmentioning
confidence: 99%